Anti-asthmatic fraction screening and mechanisms prediction of Schisandrae Sphenantherae Fructus based on a combined approach - Li, Fan; Li, Bin; Liu, Jiushi; Wei, Xueping; Qiang, Tingyan; Mu, Xinlu; Wang, Yumeng; Qi, Yaodong; Zhang, Bengang; Liu, Haitao; Xiao, Peigen (Frontiers in Pharmacology, 2022)
Objective: Schisandrae Sphenantherae Fructus (SSF) is a traditional Chinese medicine used to treat coughs, pulmonary and inflammatory diseases. However, the pharmacodynamic material basis and mechanisms for SSF in asthma treatment remain unclear. This study aims to screen the anti-asthmatic fraction and verify the pharmacodynamic material basis, then predict the potential mechanism and verify the interaction ability between compounds and core targets. Methods: Firstly, three fractions of SSF were compared in terms of composition comparison and anti-asthmatic effects. Then, ultra-performance liquid chromatography-quadrupole/time-of-flight-mass spectrometry/mass spectrometry (UPLC-Q/TOF-MS/MS) strategy was used to identify the compounds from the active fraction, and the anti-asthmatic efficacy of the active fraction was further studied by ovalbumin (OVA)-induced asthma murine model. Finally, the network pharmacology and molecular methods were used to study the relationships of active compounds, core targets, and key pathways of PEF in asthma treatments. Results: The petroleum ether fraction (PEF) of SSF showed better effects and could significantly diminish lung inflammation and mitigate the level of serum immunoglobulin E (IgE), interleukin (IL)-4, IL-5, IL-6, IL-13, and IL-17 in mice. A total of 26 compounds from PEF were identified, among which the main compounds are lignans and triterpenes. Moreover, 21 active compounds, 129 overlap-ping targets, and 10 pathways were screened by network pharmacology tools. The top 5 core targets may play a great role in asthma treatment. Gene Ontology (GO) analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis suggested that PEF can treat asthma by acting on multiple asthma pathological processes, involving IL-17 signaling pathway, T helper (Th) 17 cell differentiation, and calcium signaling pathway. Molecular docking was performed to evaluate the interactions of the protein-ligand binding, and most docked complexes had a good binding ability. Conclusion: The present results might contribute to exploring the active compounds with anti-asthmatic activity.